Unpacking the Role of Job Insecurity for Employee Creativity: A Multidimensional Perspective - Qu, Hao; Walter, Frank; Zhang, Yong; Zhang, Xiaomeng (Journal of Management, 2025)
Modern organizations frequently expect their employees to exhibit high creativity while facing considerable job insecurity. Although it is often assumed that job insecurity diminishes individual creativity, the empirical findings on this relationship are not consistent. The present study aims to scrutinize this assumption and to address such inconsistencies. To do so, we cast both job insecurity and creativity as multidimensional constructs, and we examine key mechanisms and boundary conditions of their linkages. Results from both a longitudinal (Study 1) and a time-lagged multisource survey study (Study 2) illustrated a negative indirect relation between quantitative job insecurity and radical creativity via diminished career commitment. For qualitative job insecurity, by contrast, there was a negative indirect relation with incremental creativity via reduced organizational identification. Moreover, Study 2 revealed distinct moderators for these associations. Employees’ turnover risk propensity buffered the indirect connection between quantitative job insecurity and radical creativity, whereas Confucian traditionality mitigated the indirect relation between qualitative job insecurity and incremental creativity. These findings shed new light on the important role of job insecurity for individual employees’ creative performance and advance our theoretical understanding of the complexities underlying these linkages.